Competencies and Service Quality of Room Attendants: A Case Study of Hotels in Trang Province - Choosiangjeaw , Konsirak; Ragmai , Siripong (Dusit Thani College Journal, 2020)
This objectives of this research were 1) to study competency of room attendants by ASEAN Common Competency Standards for Tourism Professionals, 2) to study service quality of Room attendant for hotel in Trang, and 3) to propose the guideline of Service Quality of room attendant of hotels business in Trang. The researcher had studied 4 factors including core competency, function competency, personnel competency, and service quality. The sample groups of this qualitative research were 14 room attendants, 5 executive housekeepers, 28 guests, and 5 specialists. The room attendants and executive housekeeper participated in the in- depth interview and participant observation for the inquiry of staff competency in the angles of both room attendants and executive housekeepers, respectively; while 28 guests were interviewed in aspect of service quality. Five specialists attended the focus-group interview in order to investigate about the appropriateness of competency and service quality of room attendants. The results showed that (1) room attendants should be more educated about product knowledge in the aspect of core competency and their attitudes should be adjusted in aspects of the personnel competency. (2)on the contrary, the function competency was completed and service quality reached the customer satisfaction even if it was not covered all aspects because the customers were satisfied with staff communication. (3) according to this study, each should propose their own guidelines in developing the service quality among room attendants as each hotel has located in different locations and has different circumstance